APLIKASI IMC BERBASIS STRATEGI PENALAAN PENGENDALI PID DIGITAL PADA SISTEM PEMANAS UDARA - Khuriati RS, Ainie (BERKALA FISIKA, 2012)
This paper investigated an application of the methodology that was developed by Rivera, a methodology to obtain reduced-order models that satisfy the Prett-Garcıa digital PID tuningrules, using prefiltered ARX estimation as a basis. The method was applicated as the temperaturecontrol system on theair heater. IMC-PID controller is not only superior but it has a simple andgeneral structure such as that of a PID controller too.Keywords: PID digital , IMC, ARX model.